2018
DOI: 10.1007/s11748-018-0996-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surgical treatment of Masaoka stage III-IV thymic epithelial tumors

Abstract: Patients with Masaoka stage III-IV thymic epithelial tumor showed relatively favorable long-term survival after surgical treatment. Therefore, aggressive surgical resection for complete resection may be a treatment option for these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Because SVC replacement is a technically challenging operation, even at a high-volume center, the management of locally advanced TETs is still a matter of debate among surgeons, oncologists, and radiotherapists. 10,11 The assessment of resectability depends mostly on the surgeon's judgment and experience but should be discussed by a multidisciplinary team for a more comprehensive overview. A meticulous preoperative workup allows accurate staging of the disease, functional evaluation of the patient, and planning of the surgical strategy.…”
Section: Commentmentioning
confidence: 99%
“…Because SVC replacement is a technically challenging operation, even at a high-volume center, the management of locally advanced TETs is still a matter of debate among surgeons, oncologists, and radiotherapists. 10,11 The assessment of resectability depends mostly on the surgeon's judgment and experience but should be discussed by a multidisciplinary team for a more comprehensive overview. A meticulous preoperative workup allows accurate staging of the disease, functional evaluation of the patient, and planning of the surgical strategy.…”
Section: Commentmentioning
confidence: 99%
“…However, it can be found that surgery plays an important role in the treatment of stage III thymic tumors. Studies have shown that complete resection is the most important prognostic factor for stage III thymic tumors ( 9 , 14 ). Therefore, resectability of all stage III thymic tumors should be evaluated preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…( 5 - 8 ). In general, however, surgical treatment is the preferred option for resectable lesions, as numerous studies have demonstrated that complete resection of the tumor is the most important prognostic factor for thymic tumors ( 5 , 9 , 10 ). With the advancement of minimally invasive surgery, doctors have used video-assisted thoracoscopy (VATS) ( 10 ), even robotic VATS ( 11 ), to remove stage III thymic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…13,19 In bilateral graft cases, besides smaller size, attention needs to be paid on the matches of diameter of both graft vessels, preventing the occurrence of blood stealing, which could result in blood flow reduction in the small vessel and even thrombus formation. 20,21 Our experience for bilateral reconstruction is that the artificial vessel in 1.2 to 1.4 cm diameter is suitable to replace right BCVor SVC, and 1.0 to 1.2 cm fitting for left BCV. In addition, the diameter difference between the two grafts should be within 0.4 cm.…”
Section: Surgery Procedures Recommended and Grafts Selectedmentioning
confidence: 99%